2023
DOI: 10.3390/ijms24108927
|View full text |Cite
|
Sign up to set email alerts
|

αvβ3 Integrin as a Link between the Development of Fibrosis and Thyroid Hormones in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc) is an autoimmune disease characterized by fibrosis of the skin and internal organs. Key players mediating fibrosis are myofibroblasts (MF) that, following transforming growth factor β (TGFβ) exposure, produce a collagen-rich extracellular matrix (ECM) that induces myofibroblast differentiation. Myofibroblasts express αvβ3 integrin (a membrane receptor for thyroid hormones) and miRNA-21 that promotes deiodinase-type-3 expression (D3), causing the degradation of triiodothyronine (T3) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Recently, αvβ3 integrin has been identified as a crucial link between fibrosis development and thyroid hormones (THs) in SSc. The finding suggest that the integrin exerts its function by deregulating THs binding site regulation 25 . Previous studies have demonstrated elevated levels of the Th1 chemokine CXCL10 in serum or tissue, which may play a key factor in systemic rheumatologic diseases 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, αvβ3 integrin has been identified as a crucial link between fibrosis development and thyroid hormones (THs) in SSc. The finding suggest that the integrin exerts its function by deregulating THs binding site regulation 25 . Previous studies have demonstrated elevated levels of the Th1 chemokine CXCL10 in serum or tissue, which may play a key factor in systemic rheumatologic diseases 26 .…”
Section: Discussionmentioning
confidence: 99%